Risks at commercial banks and some recommendations for Vietnamese commercial banks - Nga, Nguyen Thi Tuyet (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2023)
The recent consecutive banking crises in the world have raised concerns about a global financial crisis like what happened more than a decade ago. Facing the risk of possible crises due to political and social instability globally, what should Vietnam prepare to avoid a crisis in the banking system or to be ready to respond if a crisis occurs? This article research banking crises, analyzes risks in banking system and proposes recommendations to avoid banking crises.